2012
DOI: 10.1155/2012/487380
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Enriched Fraction ofPhyllanthus emblicaPotentiates Indomethacin-Induced Gastric Ulcer Healing via e-NOS-Dependent Pathway

Abstract: The healing activity of gallic acid enriched ethanolic extract (GAE) of Phyllanthus emblica fruits (amla) against the indomethacin-induced gastric ulceration in mice was investigated. The activity was correlated with the ability of GAE to alter the cyclooxygenase- (COX-) dependent healing pathways. Histology of the stomach tissues revealed maximum ulceration on the 3rd day after indomethacin (18 mg/kg, single dose) administration that was associated with significant increase in inflammatory factors, namely, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
1
35
0
3
Order By: Relevance
“…Our previous report presents that ethanolic extract of fruits of P. emblica showed antiulcer activity at a dose dependent manner mainly through its antioxidative properties by modulation of IL-10 level [71]. We have also reported that a fraction of the active component of ethanolic extract of fruits of P. emblica showed antiulcer activity by modulation of COX [72] or NOS pathway [73].…”
Section: Phyllanthus Emblica Phyllanthus Emblica L or Emblica Officmentioning
confidence: 93%
“…Our previous report presents that ethanolic extract of fruits of P. emblica showed antiulcer activity at a dose dependent manner mainly through its antioxidative properties by modulation of IL-10 level [71]. We have also reported that a fraction of the active component of ethanolic extract of fruits of P. emblica showed antiulcer activity by modulation of COX [72] or NOS pathway [73].…”
Section: Phyllanthus Emblica Phyllanthus Emblica L or Emblica Officmentioning
confidence: 93%
“…The SOD was estimated based on the generation of superoxide radicals produced by xanthine and xanthine oxidase, which react with nitro blue tetrazolium to form Formosan dye. The SOD activity was then measured at 560 nm by the degree of inhibition of this reaction and was expressed as mmol/min/mg tissue [12].…”
Section: Measurement Of Gastric Enzyme Activitymentioning
confidence: 99%
“…12 Also, A. racemosus has shown to heal duodenal ulcers without inhibiting acid secretion which indicates that it may have cytoprotective action similar to that of prostaglandin. 8 The effect of increase in gastric motility by Phyllanthus emblica and Asparagus racemosus can also be explained by its effect on prostaglandin.…”
Section: Discussionmentioning
confidence: 99%